Leave-Taking Formulas in Contemporary Russian Language - Victoriya Trubnikova (Studi Slavistici)
This article investigates strategies of leave-taking behavior in contemporary Russian. After reviewing recent literature on leave-taking formulas, with a particular focus on Russian, the article presents the results of a pilot study examining farewell expressions and conversational moves. Data were collected using a purpose-designed questionnaire that elicited situationally bound responses and compiled a pool of words, expressions, and sayings that speakers reported using when saying goodbye to both acquaintances and strangers. The results support the hypothesis that parting interactions are context-sensitive rather than fixed. The choice of terminal exchange formulas and supportive moves varies depending on factors such as the degree of familiarity, the time elapsed since the previous encounter, and the anticipated duration of separation.